Analisa Perhitungan Cadangan Minyak Lapisan Reservoir “X” Pada Lapangan “NBL-14” Dengan Metode Material Balance Menggunakan Simulator MBAL - Nabila Adhelia Maulidha; Firdaus; Nijusiho Manik; Sri Konsep Harum Wicaksono; Jan Friadi Sinaga; Abiyyu Caesar Bimoseno (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2021)
The calculation of reserves is critical in petroleum engineering because knowing the amount of reserves contained in a reservoir allows one to determine the feasibility of a field. A field that is declared economically viable and can be produced is obtained from the many oil reserves that exist in the reservoir. Therefore, a field's reserves will be calculated. In this research, the calculation of reserves is carried out using the material balance method using the MBAL simulator. The material balance method is used to determine the quantity of reserves in a developed field's reservoir. The material balance method requires parameters including PVT data, tank data, production data, and history in the field. The result of calculation using the material balance method using the MBAL simulator obtained an OOIP value of 112.238 MMSTB with the type of drive mechanism in the